An Economic Analysis of Updating and Expanding School Breakfast Program Offerings in High Schools. (1st April 2019) - Shanafelt, Amy; Magliocco, Brandon; Milbrath, Kathleen; Nanney, Marilyn (Susie); Caspi, Caitlin
ABSTRACT: BACKGROUND: School breakfast is an important nutritional component of a student's day. Many schools operate a school breakfast program, but high schools have low rates of participation. This study aimed to investigate the economic impact on school food service, of expanding the school breakfast program to increase participation in high schools. METHODS: Ten rural high schools participated in the economic analysis of expanding their school breakfast program. Schools provided data on costs of daily operation and start‐up costs. Analyses calculated the daily breakeven point, revenue, cost, and days needed to recoup costs. RESULTS: Schools sold enough breakfast meals to break even on daily costs of operating an expanded program. Schools saw daily profits ranging from $196–$432 and recouped costs associated with expanding the breakfast program within 15–46 days. CONCLUSIONS: Expanding the school breakfast program can be economical for schools, while increasing student exposure to the health and academic benefits of school breakfast.